A practical approach of urban green infrastructure planning to mitigate urban overheating: A case study of Guangzhou. (10th March 2021) - Wang, Yafei; Ni, Zhuobiao; Hu, Mengmeng; Chen, Shaoqing; Xia, Beicheng
Abstract: With the rapid economic development and tremendous urban expansion, cities frequently experience overheating problem. Urban green infrastructure (UGI) has proved effective in alleviating urban warming and enhancing thermal comfort. However, few research has been conducted to determine the proper UGI strategy across scales. Here, we propose a sustainable strategy for UGI planning by synthesizing the local climate zone (LCZ) concept and microclimate simulation, with the goal of ameliorating surface urban heat island (SUHI) and improving thermal comfort in cities. The LCZ map of Guangzhou showed that the major 'built-up land types' concentrated in the central area with high land surface temperature (LST) and intensities of SUHI. The circles (1-km diameter) identified as LCZ 2, 3, and 8 were recognized as planning areas by considering the intensities of SUHI and practicability. Afterward, the simulations of the UGI strategy scenarios at three randomly selected sample sites in LCZ 2, 3, and 8 were carried out using the ENVI-met model. The case study results in Guangzhou showed that increasing the green cover to 10% by adding grove and street trees could be the best adaptation strategy to ameliorate overheating, whereas adding extensive green roofs aggravated SUHI to a certain extent and showed minimal impacts on the thermal comfort at a pedestrian level. We show that it is promising to combine the LCZ concept and ENVI-met simulation in optimizing UGI toward urban overheating mitigation. Highlights: Multi-scale & discipline UGI strategy is needed to mitigate urban overheating. A practical approach synthesizing LCZ concept and ENVI-met simulation was proposed. Major built types concentrated in the central area with high intensities of SUHI. Adding grove and street trees was the best adaptation strategy. Application value of adopted approach was underlined for subsequent UGI studies.